2020
DOI: 10.3389/fimmu.2020.586111
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetics at the Intersection of Autoimmunity and COVID-19: A Potential Key for Heterogeneous COVID-19 Severity

Abstract: COVID-19 presentation is very heterogeneous across cases, and host factors are at the forefront for the variables affecting the disease manifestation. The immune system has emerged as a key determinant in shaping the outcome of SARS-CoV-2 infection. It is mainly the deleterious unconstrained immune response, rather than the virus itself, which leads to severe cases of COVID-19 and the associated mortality. Genetic susceptibility to dysregulated immune response is highly likely to be among the host factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 87 publications
1
35
0
1
Order By: Relevance
“…Host genetics also contributes to aberrant immunity in autoimmune diseases and susceptibility to infectious diseases in humans and such variants are often found in genes involved in the immune response and inflammation [44,45]. The current knowledge and our work confirm these findings in COVID-19 [41,43,45,57,58]. Autophagy genes have recently been proposed as susceptibility factors in COVID-19 [46].…”
Section: Discussionsupporting
confidence: 84%
“…Host genetics also contributes to aberrant immunity in autoimmune diseases and susceptibility to infectious diseases in humans and such variants are often found in genes involved in the immune response and inflammation [44,45]. The current knowledge and our work confirm these findings in COVID-19 [41,43,45,57,58]. Autophagy genes have recently been proposed as susceptibility factors in COVID-19 [46].…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, we have previously published two articles to justify the use of NSAIDs including diclofenac potassium and ibuprofen for early management of COVID-19 [ 32 , 33 ]. We suggested that NSAIDs might prevent, especially when early administered, or reverse COVID-19 associated hyperinflammatory response which is correlated with the immuno-pathologically induced SARS CoV-2 morbidity and mortality [ 5 ] and to prevent the cytokine induced lymphocyte distraction into or away from the lungs that is laboratory manifested through lymphopenia [ 32 ].…”
Section: Nsaids Potential Therapeutic Role In Management Of Covid-19mentioning
confidence: 99%
“…Interestingly and more clinically important, an exaggerated inflammatory response was described as the culprit of the majority of COVID-19 deaths and it was attributed to a weak, irregular or inhibited early interferon response to SARS CoV-2 infection that causes an excessive viral replication triggering this exaggerated inflammatory response and leading to unconstrained immune response which is responsible for COVID-19 associated mortality, rather than the virus itself [ 5–7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it can be used to represent a variety of differences in viral genotypes, i.e., phylogenetic diversity, and putatively related endo-and phenotypes including those that may emerge during SARS-CoV-2 pandemic (127)(128)(129)(130). Instead of the viral genotype, host genetic risk factors of COVID-19 (131)(132)(133)(134) and their endotype and phenotype relations can be illustrated. Accordingly, endotypes can consist, for instance, in various immune evasion strategies and clinical phenotypes in any patient outcome.…”
Section: Possible Cellular Sources Of Il-10 In Covid-19mentioning
confidence: 99%